Animal Models for COVID-19 Therapeutic Development: Where We Are and Where We Need to Go - Zhao, Sihai; Fan, Jianglin; Liu, Enqi (Frontiers in Microbiology, 2022)
The coronavirus disease 2019 (COVID-19) has become a global epidemic disease. Scientists have generated many different animal models, including non-human primates, mice, hamsters and ferrets, to study the mechanisms of COVID-19 and develop potential therapeutics. In this minireview, we summarize the recent progress on COVID-19 animal models and report their characteristics and applications. We would like to share the information with laboratory animal experts who are involved in COVID-19 research and discuss about the prospects on the direction of generating or using new models.